Challenges and Strategies of Law Enforcement in Eradication of Money Laundering in Indonesia - Karyono Karyono; Evita Isretno Israhadi (Greenation Research & Yayasan Global Resarch National, 2025)
One type of economic crime that significantly affects both the integrity of the legal system and the financial viability of a country is money laundering (TPPU). This phenomenon is increasingly complex with advances in financial technology, which makes it easier for criminals to disguise the origins of criminal assets. This study aims to analyze the challenges and strategies for law enforcement against financial technology-based money laundering in Indonesia, using a normative legal approach through a review of applicable laws and regulations, doctrines, and legal policies. The study's findings show that, particularly when it comes to exchanging information and demonstrating the provenance of assets, coordination between law enforcement organizations like the Financial Transaction Reports and Analysis Center (PPATK), the Financial Services Authority (OJK), the Police, and the Prosecutor's Office is still not at its best. Furthermore, Article 2 paragraph (1), Article 3, Article 4, and Article 5 of Law Number 8 of 2010 addressing TPPU have been canceled by the implementation of the new Criminal Code through Law Number 1 of 2023, so that harmonization of norms is needed to avoid a legal vacuum in its implementation. Future law enforcement strategies need to be directed at strengthening regulations that adapt to technology, increasing the capacity of law enforcement officers, and fostering cross-sector collaboration to strengthen reporting and prevention systems. Active public participation in anti-money laundering education is also a crucial element in creating a transparent and equitable legal system in the digital age.